Vivências como estudante de medicina da UFSCar: narrativa reflexiva - Catelani, Gabriela Rios (Universidade Federal de São Carlos, 2021)
As stated in the pedagogical project of the UFSCar Medicine course, the course conclusion work must be a reflective synthesis of moments during the student's graduation, contemplating teaching, assistance, extension, and research. This work is divided into topics: cycle I, cycle II, cycle III, electives, and complementary activities, which I carried out as a medical student, demonstrating my growth and professional training over the years.
Experiences as a medicine student at UFSCar: reflective narrative
Keywords: Medicina; UFSCar; Síntese; Medicine; Synthesis; CIENCIAS DA SAUDE